Digital Transformation in Environmental Security Management in Calosa Cluster, Bandung Regency - Surya Michrandi Nasution; Reza Rendian Septiawan; Ardiansyah Ramadhan (CogniSpectra Publishing, 2025)
Background: This community service activity aims to enhance environmental security in residential areas through digital transformation by integrating technology and community empowerment. Conducted at the Calosa Cluster, Bandung Regency, this program was initiated due to frequent losses and the limited effectiveness of existing surveillance systems, especially in blind spots. The objective is to develop a sustainable and community-managed security system using modern surveillance technology. Contribution: This program contributes to the community by increasing residents' sense of security, enhancing technological literacy, and fostering collective responsibility in managing neighborhood safety. Method: A participatory and collaborative approach was applied, involving residents, housing managers, and a university implementation team. The method included needs analysis, planning, training, and system installation. Surveys and interviews were conducted to identify security gaps, followed by the installation of devices and training on CCTV operation and data management. Results: The implementation successfully improved surveillance coverage and reliability. Residents gained practical skills to operate and manage the system independently. The positive response indicated a strengthened sense of security and community involvement. Conclusion: The program successfully addressed the security challenges in the Calosa Cluster through a digitally based, community-oriented solution. It demonstrates that integrating technology and community participation can create an effective, sustainable environmental security model applicable to similar residential areas.